Which cognitive training intervention can improve young drivers' speed management on the road?. (January 2019) - Molloy, Oleksandra; Molesworth, Brett R.C.; Williamson, Ann
Highlights: Cognitive-based training was associated with reduced young driver speeding behaviour. Combined feedback was most effective in reducing young drivers' speeding behaviour. Self-explanation improved young drivers' speeding behaviour. Combined feedback with self-explanation improved young drivers' speeding behaviour. Auditory alert feedback failed to improve young drivers' speed management behaviour. Abstract: The current study examined the effectiveness of two cognitive based training methods, namely Feedback and Self-explanation in improving young drivers' speed management behaviour in the operational environment. Seventy-five participants, all provisional licence holders under the age of 25 years completed three on-road drives in an instrumented vehicle. In the first drive (baseline), participants randomly assigned to the Auditory Alert Feedback group were provided an auditory alert when they exceeded the posted speed limit. In the Combined Feedback group, participants following the baseline drive were provided feedback about the number of times they exceeded the speed limit, the financial penalties associated with such behaviour, and the safety implications. Participants in the Self-explanation group were asked to explain to themselves their performance, in terms of speed management following the baseline drive. Participants randomly assigned to the Control group experienced no such intervention. The results revealed in the test drive immediately after the baseline drive, and one week post baseline test drive, combined feedback was most effective in reducing the average speed and percentage of time speeding in both the low-speed (50 km/h) and high-speed (80 km/h) zones. Self-explanation with or without combined feedback produced better speed management than control and auditory alert feedback, but was found to be less effective than the combined feedback. These findings provide valuable insight into the effectiveness of cognitive-based training programmes such as Feedback and Self-explanation in improving young drivers' speed management behaviour. They also highlight the relative ineffectiveness of auditory alert feedback in improving young drivers' speed management.